2008
DOI: 10.1063/1.2980056
|View full text |Cite
|
Sign up to set email alerts
|

Self-consistent generalized Kohn-Sham local hybrid functionals of screened exchange: Combining local and range-separated hybridization

Abstract: We present local hybrid functionals that incorporate a position-dependent admixture of short-range ͑screened͒ nonlocal exact ͓Hartree-Fock-type ͑HF͔͒ exchange. We test two limiting cases: screened local hybrids with no long-range HF exchange and long-range-corrected local hybrids with 100% long-range HF exchange. Long-range-corrected local hybrids provide the exact asymptotic exchange-correlation potential in finite systems, while screened local hybrids avoid the problems inherent to long-range HF exchange in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
68
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(68 citation statements)
references
References 94 publications
0
68
0
Order By: Relevance
“…This approach has an increasing popularity ("generalized KohnSham" approach) due to its relative simplicity compared to the rigorous optimized effective potential method. 29 All the terms of the B05 potential matrix, F, are readily available except those coming from the ND correlation components, Eqs. (8) and (9), μ and ν below are basis function indices …”
Section: Dealing With the Discontinuities In The B05 Functional Amentioning
confidence: 99%
“…This approach has an increasing popularity ("generalized KohnSham" approach) due to its relative simplicity compared to the rigorous optimized effective potential method. 29 All the terms of the B05 potential matrix, F, are readily available except those coming from the ND correlation components, Eqs. (8) and (9), μ and ν below are basis function indices …”
Section: Dealing With the Discontinuities In The B05 Functional Amentioning
confidence: 99%
“…[42,51] (2) Position dependence: in local hybrid functionals developed by Scuseria et al, the mixing parameter is determined as a function of the electron density at each point in space, thereby avoiding the need of empirical parameters. [52][53][54][55] (3) Perturbation theory: the mixing parameter used in the Perdew-Burke-Ernzerhof hybrid functional (PBE0) and the Heyd−Scuseria−Ernzerhof (HSE) functional (an approximation of the former) is 25%, [45,56] which was determined analytically via perturbation theory. [57,58] Subsequent benchmarks showed that HSE predicts accurate thermochemical properties for molecular test sets (G2), [45] and good band gaps for simple semiconductors such as C, Si, BN, BP, SiC, β-GaN, GaP, and MgO with a mean absolute error (MAE) of 0.2 eV, which is much better than either LDA and PBE (MAE: ~1.4 eV).…”
Section: Introductionmentioning
confidence: 99%
“…Perdew et al [42] pointed out that such behavior hinders the correct description of space dependent phenomena. To overcome this shortcoming the so called local hybrids were suggested [43][44][45][46][47][48][49].…”
Section: Introductionmentioning
confidence: 99%